Diagnostic Accuracy of Elastography to Differentiate Between Malignant and Benign Lymph Nodes of Neck and Head Region Taking Histopathology as Gold Standard - Hina Baig, Muhammad Shafiq Ul Azam, Aysha Akram, Asim Ali, Aisha Asim, Rabia Younas, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: The analysis of superficial lymphadenopathy in the cervical, axillary, and inguinal regions is vital in planning therapy for patients. Elastography is a technique currently being used for the evaluation of lymph nodes by means of evaluating tissue elasticity. In medical practice, shear wave-based and strain elastography techniques are being utilized. Strain elastography can be used to assess types of elasticity. Colors inside and around the nodes are estimated in the first place and then a 4-5 scale scoring system is used to score them visually. The present study aimed to assess the diagnostic accuracy of elastography in distinction between malignant and benign lymph nodes of the neck and head region, taking histopathology as the gold standard. Methods: This study was carried out on ninety-six (96) patients of either gender with lymph nodes in the head and neck region admitted to Children Hospital and University of Child Health Sciences Lahore and Mardan Medical Complex. Patients with proven histopathology and gone through surgery in the head and neck region were excluded from the study. Each patient was subjected to the high-resolution elastography with a 7.5 MHz linear array probe. A consultant radiologist performed the elastography in the presence of the researcher and noted the lymph node types. The histopathology report was compared with the findings of elastography. Results: High-resolution elastography was conducted on each patient enrolled in this study and their results were categorized into two distinct groups’ namely positive elastography and negative elastography. In the positive group, malignant lymph node diagnoses were supported in 51 patients by elastography. Out of which 46 were true positive cases and 5 were false-positive cases with no malignant histopathology. Similarly, in elastography, negative patients, only 3 cases were false negative and 42 cases were true negative. The overall diagnostic precision, specificity, negative predictive value, positive predictive value, and sensitivity of elastography was found to be 92%, 89.10%, 92.80%, 89.40%, and 94%, respectively, in order to differentiate malignant lymph nodes from benign lymph nodes in the neck and head region, taking histopathology as the gold standard. Conclusions: The present study demonstrated that elastography is a favorable and invasive technique for the diagnosis and differentiation of malignant lymph nodes from benign lymph nodes with high diagnostic accuracy. It may help in selecting surgical procedures for lymph nodes in the neck and head region. Keywords: Elastography, Sensitivity, Malignant Lymph Nodes.